Peran Pusat Pelaporan dan Analisis Transaksi Keuangan (PPATK) dalam Pencegahan dan Pemberantasan Tindak Pidana Pendanaan Terorisme - Ayu Putu Mira Fajarini; I Made Minggu Widyantara; I Nyoman Sutama (Warmadewa Press, 2022)
The financing of terrorism is a serious issue that needs to be addressed. In this case, PPATK as the FIU in charge in Indonesia has a role and function to carry out countermeasures for terror financing in accordance with Law no. 8 of 2010 or other regulations. The purposes of this study are to reveal the efforts of the financial transaction reporting and analysis center (PPATK) in preventing and eradicating criminal acts of terrorism financing as well as the obligations of Bank Indonesia in efforts to prevent and eradicate money laundering and terrorism financing. This study uses a normative research method with a statutory approach. The sources of law used are primary and secondary with the technique of collecting legal materials, which is carried out in the library and the data that has been collected is then used qualitative analysis techniques. The results of the study reveal that in an effort to prevent and eradicate criminal acts of terrorism financing, in general PPATK has two efforts, namely juridical and non-juridical. Juridical efforts are efforts to detect money laundering crimes, provide punishment for terrorist actors, implement a follow the money approach, and confirm blocking actions against funds operated. Meanwhile, non-juridical efforts are efforts to release innovations in the form of SIPENDAR and agree to the signing of the MoU on cooperation between the Financial Intelligence Unit (FIU) by Indonesia and Australia. Bank Indonesia has an obligation to submit reports to PPATK in the form of Suspicious Financial Transaction Reports, Cash Financial Transaction Reports, and Financial Transaction Reports of funds that take place abroad.